Lexical-semantic characteristics of banking terms in modern hindi language - Турар, А. C.,; Кокеева, Д. М. (Journal of Oriental Studies, 2018)
Сonsidering and analyzing the origins of banking terms in Hindi language, it was revealed the borrowing words of the banking sector from many other languages. In particular, words from Sanskrit, Arabic, Persian, English languages are open system that interact with other layers of vocabulary. In Banking there are a number of specific features that affect their banking terms. The using of terms are provided by the employees of banking sector. Banking terms in Hindi were systematized depending on the services provided by the Bank. Banks provide the following services: loan processing, account opening, registration of payment cards, opening deposit, money transfer. For the above Bank`s services was considered banking terms.